BENEFICIAL OWNERSHIP: TRANSPARENCY AS AN EFFORT TO PREVENT AND ERADICATE MONEY LAUNDERING AND ITS IMPACT ON INVESTMENT MARKETS - Jacqueline Anastasia Sihombing (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
Transparency plays a crucial role in the prevention and eradication of money laundering, a significant threat to financial system stability and economic integrity. This study aims to analyze the significance of beneficial ownership in achieving transparency, particularly in the context of preventing and eliminating money laundering. It explores the impact of transparency on the investment market and identifies necessary efforts and policies to enhance transparency. Transparency is a critical factor for investors in making informed decisions and reducing risks within the investment market. Using the normative juridical method, this study reveals that disclosing information about beneficial owners has a positive effect on preventing and combating money laundering crimes. Improved transparency enables more effective identification of risks and violations, leading to appropriate preventive measures. Furthermore, greater transparency positively influences the investment market, as investors tend to trust and feel motivated to invest in an environment where information about ownership and asset utilization is readily accessible. This fosters investor confidence, strengthens market integrity, and promotes economic growth. Effective transparency necessitates collaboration among authorities, financial institutions, and participants in the investment market. Implementing clear and robust regulations is crucial, alongside fostering corporate awareness and fostering a strong commitment to transparency.